Lack of patient education is risk factor of disease flare in patients with systemic lupus erythematosus in China - Le Zhang; Wei Luan; Shikai Geng; Shuang Ye; Xiaodong Wang; Liping Qian; Yang Ding; Ting Li; Anli Jiang (BMC, 2019)
Abstract Background To explore the inadequacies of health service and its impact on clinical outcomes of patients with systemic lupus erythematosus (SLE) in China. Methods A total of 210 SLE patients were randomly recruited between January 2017 and January 2018. Each patient received self-report questionnaires to assess medication adherence [Compliance Questionnaire for Rheumatology (CQR)], beliefs about medicines [Beliefs about Medicines Questionnaire (BMQ)] and satisfaction about medicine information [the Satisfaction with Information about Medicines Scale (SIMS)]. Associations between SLE disease activity index (SLEDAI-2 K) and observed factors were analyzed by multiple logistic regression. Results Based on CQR, only 28.10% patients were adherent. The score of BMQ was 2.85 ± 5.42, and merely 32.38% patients were satisfied with the information about their prescribed medicines. Disease activity was associated with SIMS, EuroQol five-dimensions [EQ5D], Systemic Lupus International Collaborating Clinics (SLICC), depression, use of NSAID (P ≤ 0.05). Remission of disease was positively correlated with SIMS (OR = 0.16, 95% CI: [0.06, 0.40]), and BMQ (OR = 0.64, 95%CI: [0.43, 0.94]). Conclusion In this study, the scores of BMQ and SIMS were low, implying defects in the patient education of health service system, which led to disease flare in Chinese SLE patients. Trial registration ClinicalTrials.gov ID: NCT03024307. Registered January 18, 2017.